Materials for battery applications - Toh, Jun Jie (2018)
Energy storage technology has been progressing constantly to meet the rising energy demand in a technologically-driven society today. One such progress is advancement in technology that makes developing nanomaterials for battery applications possible. This final year project focuses on synthesising a series of V2O3/G composite powders using a sol-gel approach with ammonium metavanadate, reduced graphene oxide and different concentrations of citric acid (0.0M, 0.1M, 0.3M and 0.5M), and investigating its structural features and electrochemical performance in a lithium-ion battery anode. The materials were analysed using x-ray diffraction, field emission scanning electron microscopy, and Brunauer-Emmett-Teller formulation for the analysis of surface area and porosity. Its electrochemical performance would be measured by the use of cyclic voltammetry and galvanostatic charge-discharge cycling techniques. As anodes of lithium-ion battery, V2O3/G composite electrodes exhibit an increase in capacity with increasing concentrations of citric acid due to declining crystallinity. The initial discharge capacities for the electrodes with 0.0M citric acid and 0.5M citric acid are 211.9mAhg-1 and 1096.7mAhg-1 respectively, with a current density of 50mAg-1. In addition, the role of reduced graphene oxide provides the increase in capacities after prolonged cycling as it displays a capacity growth from 400.0mAhg-1 in the 20th cycle to 450.6mAhg-1 in the 50th cycle for the composite electrode with 0.3M citric acid.